2020
DOI: 10.1111/crj.13197
|View full text |Cite
|
Sign up to set email alerts
|

Increased p300/CBP expression in acute respiratory distress syndrome is associated with interleukin‐17 and prognosis

Abstract: Purpose Transcription co‐activator p300/CBP, a histone acetyltransferase, has a central role in tumours, inflammation and neurodegenerative diseases. We investigated the effect of p300/CBP and its association with various IL‐17‐related indicators and prognosis in patients with acute respiratory distress syndrome (ARDS). Materials and Methods We enrolled 45 adult ARDS patients who were followed for 28 days and 22 healthy controls. The mRNA expression of p300, CBP, RORγt and Foxp3 and the plasma levels of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Accumulating evidence suggests that various types of AKI, including ischemia-reperfusion injury [40], endotoxin-induced injury [41], or folic acid-induced injury [42], are associated with changes of histone acetylation in response to renal stress. Among members of HATs, p300 has been shown to play an important role in the pathophysiology of various diseases, including cancers, neurodegeneration, and inflammatory diseases [20][21][22][23]. However, the role of p300 in cisplatin-induced renal injury remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that various types of AKI, including ischemia-reperfusion injury [40], endotoxin-induced injury [41], or folic acid-induced injury [42], are associated with changes of histone acetylation in response to renal stress. Among members of HATs, p300 has been shown to play an important role in the pathophysiology of various diseases, including cancers, neurodegeneration, and inflammatory diseases [20][21][22][23]. However, the role of p300 in cisplatin-induced renal injury remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, p300 can directly bind to transcription factors, such as nuclear factor-κB (NF-κB) and p53, and regulate their activities via acetylation [17][18][19]. Accumulating evidence demonstrates that aberrant expression and/or activity of p300 are critically involved in various pathological conditions, including cancers, neurodegeneration, and inflammatory diseases [20][21][22][23]. It has also been shown that p300 promotes oxidative stress and inflammation in animal models of diabetic nephropathy [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…N-Methyl-adenosine modification of Trim59 RNA was protective against the risk of developing ARDS during sepsis [ 143 ]. The mRNA levels of p300, CREB binding protein, tyrosine-protein kinase transmembrane receptor γt, and plasma concentration of IL-17, IL-6 were higher in patients with acute ARDS compared with controls, whereas p300/CBP expression was a risk factor for 28-day mortality [ 144 ]. All these studies, although at a preliminary stage of transcriptomics research in ARDS, demonstrate that investigations are advancing rapidly and could be a valuable support to identify biological phenotypes, thus helping to better understand the pathophysiology of ARDS and provide potential new targets for the development of effective RCTs on a specific subphenotype of patients with ARDS.…”
Section: Omics In Ards Researchmentioning
confidence: 99%
“…Among HATs, p300 is perhaps the most widely studied protein that is associated with the transcriptional activation of numerous genes in response to cellular signaling. The increased activity and expression of p300 were shown to associate with different diseases, including pulmonary fibrosis [ 64 ] and acute respiratory distress syndrome [ 65 ], and reported in different types of cancers [ 65 , 66 , 67 , 68 ]. Moreover, the genetic deficiency and pharmacological inhibition of p300 were shown to abrogate pulmonary fibrosis both in vitro and in vivo [ 64 , 69 ].…”
Section: Epigenetic Dysregulation In Ipf and Copdmentioning
confidence: 99%